Analisis Penambahan Bacterial Cellulose Nanocrystals (BCNCs) Terhadap Membran Ultrafiltrasi Berbasis Selulosa Asetat - Dwifa Nuril ‘Alimah (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2024)
Cellulose nanocrystals (CNC) are used as membrane additives that can improve the polymer properties of the membrane with better performance. The addition of CNC as a hydrophile additive into the membrane polymer matrix acts as a pore forming agent. One of the potential materials for CNC production is bacterial cellulose (BC). Hydrolyze of bacterial cellulose using sulfuric acid will produce bacterial cellulose nanocrystals (BCNCs). The addition of different BCNCs content (0,1; 0,2; 0,3; 0,4; and 0,5%) in cellulose acetate (CA) ultrafiltration membrane was studied. The purpose of this study was to study the effect of BCNCs concentration on the physicochemical and performance of CA membranes. The physicochemical properties of CA membrane were characterized through measurement of density, swelling degree, and membrane porosity, membrane structure using Fourier Transform Infrared (FTIR) and contact angle measurement. Membranes with the addition of BCNCs produced CA membranes with larger and more pores, thus increasing the hydrophilicity of the membrane. This result is shown with the largest porosity shown in CA/BCNCs 0,5% of 66,2975%. This result was consistent with the largest membrane swelling degree of 300,10% and the smallest contact angle of 47o when BCNCs was added at 0,5%. The performance of CA membrane was characterized through the determination of water flux, permeability coefficient, and dextran rejection. The water flux of CA membrane increased with the increasing concentration of BCNCs added. This is shown in the highest water flux and permeability coefficient values of 58 L.m-2 .h-1 and 11 L.m-2 .h-1 .bar-1 respectively when the BCNCs loading was 0,5%. These results are in contrast to the membrane rejection coefficient which decreases with the increasing concentration of BCNCs added. This study shows the importance of using BCNCs to achieve better physicochemical properties and performance of CA ultrafiltration membranes.
Reaploud Repository Hasyim April 2026
Keywords: bacterial cellulose; hydrophilicity; membrane; nanocrystals; swelling